Deskripsi kemampuan pemecahan masalah matematika berdasarkan teori polya pada pembelajaran daring ditinjau dari gaya belajar siswa (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2021)
This research aims to describe mathematics problem solving skills based on Polya’s theory in online learning in terms of students’ learning styles. This research is qualitative research. The subject of this research is the students of class VII B SMPN 2 Kerambitan. The data collection is done by using the Kolb’s learning style questionnaire, problem solving skills test, and interview manual. Based on the trial test result for each test I and test II obtained that  which means that the instrument test is valid, for test I is equal to 0,73 and  is equal to 0,79 which means both test have high reliability,  which means that the instrument test have very good discrimination power, and  which means the instrument test have medium level of difficulty. The analysis is done by: data reduction, data display, triangulation, verification, and conclusion drawing, The result shows that: 1) diverger is the most found learning style in class VII B SMPN 2 Kerambitan, 2) diverger, assimilator, converger, and accommodator students are able to solve problem by understanding the problem, devising a plan, carrying out the plan, and looking back.
Keywords: problem solving skills; polya’s theory; online learning; learning styles